2014
DOI: 10.1371/journal.pone.0101475
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HLA Class I Haplotypes on HIV-1 Seroconversion and Disease Progression in Pumwani Sex Worker Cohort

Abstract: We examined the effect of HLA class I haplotypes on HIV-1 seroconversion and disease progression in the Pumwani sex worker cohort. This study included 595 HIV-1 positive patients and 176 HIV negative individuals. HLA-A, -B, and -C were typed to 4-digit resolution using sequence-based typing method. HLA class I haplotype frequencies were estimated using PyPop 32-0.6.0. The influence of haplotypes on time to seroconversion and CD4+ T cell decline to <200 cells/mm3 were analyzed by Kaplan-Meier analysis using SPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
2
5
1
Order By: Relevance
“…This is in agreement with the literature on disease progression and viral control [26–29], although the relationships between B*57 and disease control often appear to be more robust, suggesting that this allele may play a stronger role in clinical outcomes than viral suppression. Previous studies have reported B*45 to be associated with poor clinical outcomes of HIV infection [30] or higher HIV loads [31], but here we found that volunteers with B*45:01 were not associated with control; however, the allele remained in our final model, suggesting that it may play some role in characterizing viral control. Some studies have suggested the presence of the B*58:02 allele to be unfavorable [32]; similarly, our data suggested that persons with the allele may be less likely to control HIV (aOR, 0.5 [95% CI, .2–1.0]).…”
Section: Discussioncontrasting
confidence: 65%
“…This is in agreement with the literature on disease progression and viral control [26–29], although the relationships between B*57 and disease control often appear to be more robust, suggesting that this allele may play a stronger role in clinical outcomes than viral suppression. Previous studies have reported B*45 to be associated with poor clinical outcomes of HIV infection [30] or higher HIV loads [31], but here we found that volunteers with B*45:01 were not associated with control; however, the allele remained in our final model, suggesting that it may play some role in characterizing viral control. Some studies have suggested the presence of the B*58:02 allele to be unfavorable [32]; similarly, our data suggested that persons with the allele may be less likely to control HIV (aOR, 0.5 [95% CI, .2–1.0]).…”
Section: Discussioncontrasting
confidence: 65%
“…Due to lack of regulatory approval, characterization of host genetic background was not undertaken in this study. Past studies have shown that certain HLA class I alleles B*35, Cw*04, A*30, B*45 are linked with accelerated disease progression,[ 42 , 43 ] while alleles A*7401 and B*57 appears to be protective. [ 44 , 45 ]…”
Section: Discussionmentioning
confidence: 99%
“…The interactive effect of CD4+ T cell responses restricted by the 16 HLA class II alleles and the genetic diversity of these different HLA class II alleles could influence perinatal HIV transmission. In a previous study we have observed interactive effect of HLA class I alleles in HIV seroconversion and disease progression in the Pumwani sex worker cohort [ 37 ]. Our current study has shown the interactive effect of HLA class II genes on perinatal HIV transmission.…”
Section: Discussionmentioning
confidence: 99%